Influence of the composition of M78Si9B13 metallic glasses on their structural stability - Jakubczyk, Ewa; Stępień, Zdzisław; Jakubczyk, Mieczysław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The structural stability of Co78Si9B13 and Fe78Si9B13 metallic glasses was investigated by differential scanning calorimetry (DSC), X-ray diffraction, Hall effect and electrical resistivity methods. It was found that at first isochronal annealing leads to the formation of a-M (M = Co, Fe) phases.This process is followed by the formation of M2B phases. The phases were identified by X-ray diffraction method and their structures were confirmed with the use of quantum chemistry method. The creation of crystalline phases decreases abruptly the Hall and electrical resistivities. The alloy containing Fe appeared to have a much wider range of structural stability.
Optica Applicata, Vol. 35, 2005, nr 3, s. 339-346
Keywords: optyka; metallic glasses; crystallization; Hall effect